2022
DOI: 10.1111/ane.13610
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine in adult super‐refractory status epilepticus: Efficacy analysis on a prospective registry

Abstract: Background Status epilepticus (SE) persisting despite two anti‐seizures medications (ASM) and anesthetics is labeled super refractory (SRSE), correlating with important morbidity and mortality. Its treatment relies on expert opinions. Due to its pharmacological properties, ketamine (KET) has received increasing attention, but data are essentially retrospective. Aims To describe an unselected cohort of adults receiving KET for SRSE. Methods Analysis of a prospective registry of consecutive SE episodes, identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 19 publications
1
23
1
Order By: Relevance
“…49 Other systematic reviews on ketamine examined several clinical studies on RSE and SRSE with very heterogeneous data, highlighting the challenges of drawing valuable conclusions. [50][51][52][53] Fang and Wang concluded that ketamine appears to be effective and relatively safe for the control of multidrug-resistant RSE in children and adults. 51 Hofler and Trinka reported an overall success rate of 74% in adults and 73% in children.…”
Section: Clinical Role Of Ketamine In Se Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…49 Other systematic reviews on ketamine examined several clinical studies on RSE and SRSE with very heterogeneous data, highlighting the challenges of drawing valuable conclusions. [50][51][52][53] Fang and Wang concluded that ketamine appears to be effective and relatively safe for the control of multidrug-resistant RSE in children and adults. 51 Hofler and Trinka reported an overall success rate of 74% in adults and 73% in children.…”
Section: Clinical Role Of Ketamine In Se Treatmentmentioning
confidence: 99%
“…57 When considering ketamine dose in the reported studies, the loading dose was 1.5-5 mg/kg, with a maximum infusion rate of 15 mg/kg/h. 41,[51][52][53] In children, the bolus was 2-3 mg/kg and maintenance rate 2-7 mg/kg/h. 54,55 No Cochrane systematic reviews were found on ketamine and SE.…”
Section: Clinical Role Of Ketamine In Se Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Its results suggest that ketamine did not affect ICP even at prolonged anesthetic dosages, as do the results of a recent comprehensive analysis on non-traumatic neurological illness [ 89 ], and decreased vasopressor requirement. A 2022 prospective study with 11 patients with SRSE found lesser permanent control of SE (27%) compared to earlier retrospective studies (28–96%) [ 90 ]. Due to patient selection bias, this study may suggest that the efficacy of ketamine is not as good as other studies have demonstrated.…”
Section: Sementioning
confidence: 84%
“…19 However, in other case series the efficacy of ketamine after weaning varies significantly between 28% and 96% of cases. 20 Intravenous pentobarbital as part of a suppression-burst pattern (SBP) anesthesia for at least 72 h has proven to be effective in terminating SRSE in a small retrospective study of 31 patients with an efficacy of 90% during anesthesia. However, weaning from pentobarbital anesthesia was associated with withdrawal seizures in 50% of patients and the authors reported to have added PB to the AED scheme to allow for successful weaning thereafter.…”
Section: Discussionmentioning
confidence: 99%